A Schulman boosts its French masterbatch production capacity; reports strong fiscal 1Q 2018. Issue 2 (February 2018) - Unknown
Abstract : In France, international polymer-based materials producer A. Schulman, Inc has significantly increased capacity at its masterbatch manufacturing site in Givet. According to the company, the plant is now its largest for the production of masterbatches in Europe, the Middle East and Africa. Elsewhere, A. Schulman reported year-on-year gains in both net sales and net income in the first quarter of its 2018 fiscal year.